Sleep bruxism in children and COVID-19: An integrative review of the literature - Moreira , José Fernando Marinho de Almeida; Correia , Maria da Conceição de Barros; Cunha , Daniele Andrade da; Siva , Hilton Justino da; Santos , Leonardo Cavalcanti Bezerra dos; Marques , Kátia Maria Gonçalves; Lima , Niedje Siqueira de; Fontes , Luciana de Barros Correia (Seven Editora, 2023)
Sleep Bruxism is a movement disorder of multifactorial etiology, characterized by grinding, tapping, or clenching of teeth associated with sleep physiology. This study aimed to raise whether there is evidence of the increase in the prevalence of bruxism in children during the period of living with COVID-19. This is an integrative review of the literature by the PRISMA method and based on the guiding question: - Is there an association between the prevalence of sleep bruxism in children and COVID-19Ɂ In this context, an exploratory search was conducted through PubMed, VHL, and SciELO, considering the health descriptors or MeSH terms: "sleep bruxism", children", and "COVID-19" in Portuguese, English and Spanish versions and for the past five years as of the time of publication. The Boolean operators "AND" and "OR" were used to combine and "NOT" to exclude. These, are by the defined inclusion and exclusion criteria. The process of search and selection of records was carried out by two researchers, independently. From 181 records, only three studies were included. Only one study directly raised the association between BS and COVID-19, mentioning the increase in its incidence. DOI:https://doi.org/10.56238/emerrelcovid19-042